KARAKTERISASI SIMPLISIA DAN EKSTRAK KULIT BATANG SEKILANG (Embelia borneensis Scheff.) - Risa Supriningrum; Reksi Sundu; Triswanto Sentat; Rakhmadhan Niah; Eka Kumalasari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
The Sekilang plant (Embelia borneensis Scheff.) Is one of the plants used by the Dayak community for fishing, leech repellent and as an ingredient for hair care. Empirical use of plants can be developed into products based on natural ingredients. This must be supported by research data. As a first step, the simplicia and ethanol extract of the stem bark were characterized. The research objective was to determine the specific and non-specific characteristics of the simplicia and the extracts of the bark of the sekilang. The research stage includes plant determination, collection of raw materials, manufacture of simplicia, extract preparation, organoleptic, microscopic testing, phytochemical screening, determination of water soluble extract content, determination of ethanol soluble extract content, determination of water content and determination of ash content. Microscopy test results of sekilang stem bark showed the presence of fiber fragments, stone cells, and oxalate crystals. The average water soluble content for simplicia and sekilang bark extract was 7.5% and 80%. The average ethanol soluble content for simplicia and extract was 6% and 30%. The average moisture content for the simplicia and extract was 9.5% and 12%. The mean total ash content for simplicia and extract was 5% and 8.5%. The mean acid insoluble ash content for simplicia and extract was 1% and 0.5%.